Moral Decadence In Fitzgerald's The Beautiful And Damned (1922) A Socio-Cultural Perspective - Anggraini, Dhewi Nur (2012)
The object of this research is the novel entitled The Beautiful and Damned by F. Scott Fitzgerald. He is an author of some novels that deals with social issues for that time. The major problem of this study is how moral decadence is reflected in the novel F. Scott Fitzgerald's The Beautiful and Damned is based on Sociological approach. It occurs because there is some habituation that causes moral decadence. The researcher employs qualitative research method. In this method, the researcher uses two data resources namely primary and secondary data sources. The primary data source is the novel F. Scott Fitzgerald's The beautiful and Damned itself. The secondary data source is the books about sociology, philosophy and the other sources related to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. The structural analysis shows that in this novel F. Scott Fitzgerald delivers a message that money does not give the true happiness. The sociological analysis suggests that their is a close relationship between the production of this novel, The Beautiful and Damned, and the social realities of American Society in the 1920's.